Aplicação da tecnologia eletrocoagulação operada por corrente direta pulsada no pré-tratamento de águas eutrofiizadas do sertão central cearense - Cavalcante, Reinaldo Fontes (2020)
The search for an increase in water supply is one of the main challenges facing humanity in the beginning of the 21st century, and in this process the improvement of new technologies that aim to contribute to greater versatility of treatment at low cost is a vital strategic element. for regions with a history of quantitative and qualitative limitations of their springs, such as the central backlands of Ceará. Thus, the present work aims to study the performance of electrocoagulation, flocculation, flotation technology in multiple configurations in the pre-treatment of eutrophic waters in the Central Cearense Sertão. To this end, the monitoring and operation of an electrolytic reactor fed with water from the Pedras Brancas reservoir in Quixadá, Ceará, was carried out. A reactor divided into two parts was used: a vertical part of 4.7 liters and a horizontal part of 5.6 liters. The operation took place with the configurations using Aluminum electrodes with Parallel and Parallel Bipolar Connection, with and without the 300 rpm stirring increment and 316L Steel electrodes with Parallel and Parallel Bipolar connection with and without the 300 rpm stirring increment. Monitoring occurred with the variables of Potability Turbidity, Color, Hardness, pH, Total Coliforms and Ammonia according to Consolidated Resolution No. 5 / 2017.The treatment cost and its comparison with the conventional treatment applied to the waters of the same source were observed according to ARCE Ordinance No. 245/2018. There were significant values ​​of removal of turbidity and total coliforms in all configurations and periods analyzed, although still in disagreement with the Potability Legislation, but in order to reduce the intensity and requirements in the treatment given to these waters in the stages of filtration and disinfection. There were also significant values ​​of removal of Ammonia, Hardness and Color, this only for aluminum electrodes with compliance with the Potability legislation already in this pre-treatment stage. There were no significant differences in treatment efficiencies between configurations that used 316L Steel and Aluminum electrodes in their corresponding configurations, except for the color variable. It was noticed in the configuration of the electrolytic reactor that used electrodes and aluminum and Bipolar Parallel connection significant values ​​of removal of the monitored variables and the lowest cost compared to the modalities studied in the research. It was possible to observe that the increase in agitation in the studied configurations did not provide significant differences in the treatment given to their corresponding modalities without agitation, with an increase in energy consumption of the order of 2 to 9%. These results contribute to a greater diffusion of electrocoagulation technology in the sense of a low cost alternative for arid and semi-arid regions that have limitations regarding the use of conventional water treatment technology.